Fontan circulation causes early, severe liver damage. Should we offer patients a tailored strategy?. (15th April 2016) - Agnoletti, Gabriella; Ferraro, Gaetana; Bordese, Roberto; Marini, Davide; Gala, Simona; Bergamasco, Laura; Ferroni, Francesca; Calvo, Pier Luigi; Barletti, Claudio; Cisarò, Fabio; Longo, Filomena; Napoleone, Carlo Pace
Abstract: Background: In patients with Fontan circulation, the liver is profoundly affected by chronic venous stasis. Little is known about early hepatic changes in this population. Methods: We performed echocardiography, abdominal ultrasound, liver elastography, cardiac catheterization, esophago-gastro-duodenoscopy and calculated MELD-XI score in 64 Fontan patients (69% minors), at an interval of 1–15 years since Fontan. Results: Cardiac output remained stable in the first 5 years after Fontan, then significantly decreased (r = − 0.45, p(r = 0) = 0.003). NYHA class significantly increased after Fontan. Patients in NYHA class II/III (n = 21, 14 minors) had significantly higher hepatic pressures, but normal ventricular function and pulmonary vascular resistances (PVR). Patients with pulmonary arterial pressure (PAP) ≥ 15 mm Hg (n = 12, 6 minors) and those with PVR ≥ 2 WU*m 2 (n = 27, 25 minors), had higher hepatic pressures (p < 0.0001), a higher incidence of liver collaterals and/or esophageal varices (p < 0.0001) and splenomegaly (p < 0.02). Liver stiffness (LS) was elevated in most patients (median, 25th–75th percentile:17.3 KPa, 14.1–21.4). It rapidly increased during the first 5-years after Fontan, compared to the following 5-years (from 12.2 KPa, 9.8–14.1 to 17.5 KPa, 14.3–24.5, p = 0.007), then remained stable (19.1 KPa, 16.9–22.6, p = 0.60). MELD-XI score increased linearly with the time interval since Fontan (r = 0.31, p(r = 0) = 0.01). For patients above 12 years we found a linear correlation between LS and MELD-XI score in the 6–15 years period after Fontan (r = 0.40. p(r = 0) = 0.04). The overall incidence of established liver cirrhosis was 22%. Conclusions: This is the largest study showing that Fontan circulation prompts early, progressive and eventually irreversible liver damage. Precautions should be taken immediately after Fontan, to protect this fragile population.